Diversity and conservation of native Argentine species of Gratioleae (Plantaginaceae) - Sosa, Maria M.; Angulo, Maria B.; Amarilla, Valeria; Landi, Mauricio; Florentín, Javier E. (Phytotaxa, 2024)
The tribe Gratioleae is the richest in species of the family Plantaginaceae, with 30 genera and more than 300 species growing mainly in South America, which could be considered a center of diversity. Argentina is one of the countries with the largest number of species (35 belonging to 6 genera) of the tribe. Although the Argentinean Flora and a checklist have been published, both are outdated. With this background, we presented an updated summary of the diversity of species belonging to the tribe Gratioleae in Argentina, with detailed analysis of their geographic distribution, their conservation status according to the categories established by the International Union for Conservation of Nature (IUCN), as well as an exhaustive study on the distribution of their richness and threat patterns in different ecoregions of the country. In addition, an evaluation of the proportion of threatened species in relation to Argentina’s Protected Areas (PAs) was evaluated. The results showed that species of Gratioleae were present in 14 ecoregions, distributed predominantly in the Humid and Dry Chaco, and the Alto Paraná Atlantic Forest. Eighteen species of the 37 Argentine taxa, including two endemic taxa, are categorized as threatened (VU, EN, or CR) (47%). Although some of these species are partially protected due to their distribution in PAs, others lack this protection. Our findings contribute to the knowledge of the geographic distribution of Gratioleae within the Argentine flora, and its conservation status.